Surviving the 21st century in Southeast Asia : Open & Distance Learning for Human Capital Development - Anuwar Ali (2012)
Within the last several decades, Southeast Asia has witnessed many developments in higher education. Borne of the necessity to meet 21st Century challenges that have been brought about by globalisation, international competition and rapid expansion in information and communication technology, these developments necessarily relate to Southeast Asian countries’ need to upgrade human capital to create a skilled workforce for a knowledge-based economy. Higher education in the traditional sense has not been able to cope with this demand, as resources and facilities are often limited in many developing Southeast Asian countries. However, it is now recognised that an alternative approach to higher education, such as that offered by open and distance learning, can pave the way for a more accessible, affordable and flexible means for people to attain higher education. Southeast Asia’s open and distance learning environment is fast evolving, and the region already has many established open universities; thus indicating the great potential in its advancement for, as well as contribution to, national progress by meeting workforce-related educational needs. This paper will briefly review the current open and distance learning scene in Southeast Asia and discuss how open universities can contribute to human capital development. This paper will also explore possible scenarios for the future; where open and distance learning can further the cause of lifelong learning, what changes will be needed and how international collaboration can play a part in a developing region like Southeast Asia.